Comparative changes in sugars and lipids show evidence of a critical node for regeneration in safflower seeds during aging - Zhou, Lanyu; Lu, Lijie; Chen, Chao; Zhou, Tao; Wu, Qinghua; Wen, Feiyan; Chen, Jiang; Pritchard, Hugh W.; Peng, Cheng; Pei, Jin; Yan, Jie (Frontiers in Plant Science, 2022)
During seed aging, there is a critical node (CN) where the population viability drops sharply. Exploring the specific locations of the CN in different species of plants is crucial for understanding the biological storage properties of seeds and refining seed life span management. Safflower, a bulk oil crop that relies on seeds for propagation, has a short seed life. However, at present, its biological characteristics during storage are not clear, especially the changes in metabolic capability and cell structures. Such knowledge is needed to improve the management of safflower seed life span and effective preservation in gene banks. Here, the seed survival curve of oilseed safflower under the controlled deterioration conditions of 60% relative humidity and 50°C was detected. The seed population showed an inverted S shape for the fall in germination. In the first 12 days of aging, germination remained above 86%. Prior to the CN at approximately day 10 (C10), when viability was in the “plateau” interval, seed vigor reduced at the same imbibition time point. Further analysis of the changes in sugar concentration found that the sucrose content decreased slowly with aging and the content of raffinose and two monosaccharides decreased abruptly at C10. Differentially metabolized lipids, namely lysophospholipids [lyso-phosphatidylcholine (LPC) and lyso-phosphatidylethanolamines (LPE)] and PMeOH, increased at day 3 of aging (C3). Fatty acid content increased by C6, and the content of phospholipids [phosphatidylcholines (PC), phosphatidylethanolamines (PE), and phosphatidylinositols (PI) and glycolipids [digalactosyl diacylglycerol, monogalactosyl diacylglycerol, and sulphoquinovosyl diglycerides (SQDG)] decreased significantly from C10. In addition, the activities of raffinose hydrolase alpha-galactosidase and the glyoxylate key enzyme isocitrate lyase decreased with seed aging. Confocal microscopy and transmission electron microscopy revealed shrinkage of the seed plasma membrane at C10 and the later fragmentation. Seedling phenotypic indicators and 2,3,5-triphenyltetrazolium chloride activity assays also verified that there were significant changes in seeds quality at the CN. In summary, the time point C10 is a CN during seed population aging. Before the CN, sugar and lipid metabolism, especially fatty acid metabolism into sugar, can make up for the energy consumed by aging. After this point, the seeds were irreversibly damaged, and their viability was greatly and rapidly reduced as the cell structure became increasingly destroyed.